Predictors of sustained virological response in patients with hepatitis C virus genotype 3 infection - Zarębska-Michaluk, Dorota; Lebensztejn, Dariusz; Chrapek, Magdalena; Paluch, Katarzyna; Stępień, Piotr; Kryczka, Wiesław (Clinical and Experimental Hepatology, 2016)
Aim of the study : To assess predictors of sustained virological response (SVR) in patients with chronic hepatitis C virus (HCV) genotype 3 treated with standard therapy. Material and methods: We retrospectively investigated data of 116 consecutive treatment-naïve patients chronically infected with HCV genotype 3, treated with pegylated interferon alpha (PegIFN) and ribavirin (RBV) for 24 weeks. HCV RNA at week 4 (rapid virological response – RVR) and week 12 (early virological response – EVR) were measured in 85 and 105 patients respectively. Liver biopsy data were available for 103 patients. The variables were compared between patients with an SVR and those without. Results : Overall 70.7% of patients achieved an SVR. Pretreatment factors including younger age, mild liver fibrosis as well as normal values of gamma-glutamyl transferase (GGT) and platelet count were significantly associated with higher SVR rate in univariate analysis. In the multivariate analysis only baseline platelet count > 140 000/µl and normal GGT activity were correlated with higher SVR rate. At weeks 4 and 12 HCV RNA was undetectable in 34.1% and 84.8% of patients respectively. The SVR rate was significantly higher in patients with an RVR compared to those without (p = 0.002). Only 2 patients with a rapid and early virological response did not achieve an SVR; both had negative pretreatment prognostic factors. Conclusions : In treatment-naïve patients with genotype 3 HCV infection, low baseline platelet count and elevated GGT activity were significantly associated with poor response to PegIFN and RBV. Achieving a rapid and early virological response was associated with higher likelihood of an SVR.